Effect of Over Zone Feeding on Rail Potential and Stray Current in DC Mass Transit System. (2nd March 2016) - Du, Guifu; Wang, Chonglin; Liu, Jianhua; Li, Guoxin; Zhang, Dongliang
Abstract : DC traction power system with running rails as reflux conductor has been adopted in Guangzhou Metro Line 8. During the operation of the Guangzhou Metro Line, a high rail potential has been observed, and the leakage of stray current increases significantly. Because of the electrical connectivity of the catenary, over zone feeding of traction current may exist when multiple trains run in multiple traction substations. Guangzhou Metro Line 8 suspects that over zone feeding of traction current is the major cause of the high rail potential. In this paper, a unified chain model of DC traction power system is proposed to simulate the distribution of rail potential and stray current. Field tests and simulations have been carried out to study whether over zone feeding has an impact on rail potential and stray current. Results show that over zone feeding widely exists in DC traction power system and that the rail potential and stray current can be reduced effectively by preventing the over zone feeding of traction current.